Prospects for BLER Development in the New Countries of the EU - Rudolf, Stanisław (Comparative Economic Research. Central and Eastern Europe, 2025)
The objective of the article is to determine the prospects for the development of BLER (board-level employee representation) in the new EU countries. To achieve this goal, a critical analysis of the literature on the subject and relevant legal regulations was used. In the old countries of the EU, employee representation in corporate governance bodies has a well-established position. It is generally supported by trade unions, as well as employers and their organizations. In the new EU countries, however, the situation is different. Half of these countries do not have such representation based on legal legislation. In the remaining countries, the results of the transformation period included solutions modeled on Western countries, mainly on the German experience. In the following years, however, mainly due to the 2007–2008 global financial crisis, the scope of such representation was gradually curbed. Thus, the transformation was not followed by this type of solution taking root. Employee representation in corporate governance bodies is an important element of the democratization of labor relations, and it usually brings tangible benefits to enterprises. Therefore, it is becoming extremely important to popularize it in the new EU countries. The considerations in the article lead to the conclusion that in the near future, these countries will not be able to popularize such solutions on their own; hence, the proposal to develop an appropriate EU Directive obliging member states to popularize such solutions on mandatory principles. The chances of developing such a Directive significantly increased after the United Kingdom left the EU. Of the 14 countries under consideration, as many as 9 are post-communist countries and we will devote most of our attention to them in this article.